1990
DOI: 10.5694/j.1326-5377.1990.tb126323.x
|View full text |Cite
|
Sign up to set email alerts
|

“Generic” packaging — a possible solution to the marketing of tobacco to young people

Abstract: Creating a brand image is a key part of marketing tobacco products. It makes subtle promotion of a product possible in spite of national and State barriers (such as advertising bans) through print advertising and televised coverage of international sponsored sporting events. This article argues for the introduction of mandatory generic packaging of all tobacco products as an essential component of a complete ban on tobacco advertising and promotion. The rationale for such a move is that tobacco should be treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Dr Gerry Karr appears to be the first person to have formally proposed the idea in a motion presented at a Canadian Medical Association annual general meeting in June 1986, (20) and David Sweanor, a Canadian tobacco control activist, was recommending it to politicians in 1988. (21) Over the next decade, the proposal received some attention from researchers and advocates in Australia (David Hill and Ron Borland and colleagues) (22), New Zealand (Park Beede, Rob Lawson, Mike Shepherd and Michael Carr-Gregg, (23)(24)(25)(26) and a considerable amount of attention in Canada (27,28).…”
Section: Early Advocacy For Plain Packsmentioning
confidence: 99%
“…Dr Gerry Karr appears to be the first person to have formally proposed the idea in a motion presented at a Canadian Medical Association annual general meeting in June 1986, (20) and David Sweanor, a Canadian tobacco control activist, was recommending it to politicians in 1988. (21) Over the next decade, the proposal received some attention from researchers and advocates in Australia (David Hill and Ron Borland and colleagues) (22), New Zealand (Park Beede, Rob Lawson, Mike Shepherd and Michael Carr-Gregg, (23)(24)(25)(26) and a considerable amount of attention in Canada (27,28).…”
Section: Early Advocacy For Plain Packsmentioning
confidence: 99%
“…Almost 20 years ago it was suggested that restrictions in tobacco advertising would only be partly successful as the ‘pack itself is a powerful form of advertising’ 1. These words have proved prescient as the pack has indeed emerged as the primary marketing tool in jurisdictions with tight marketing controls.…”
Section: Tobacco Packaging As Promotionmentioning
confidence: 99%
“…To create a niche for their brand, manufacturers must strive to distinguish it from a field of hundreds. They do this by creating a brand image or brand personality [ 2 ]. The brand image is the sum of the product characteristics, advertising, promotion, package design and pricing.…”
Section: Introductionmentioning
confidence: 99%